1987
DOI: 10.1126/science.238.4830.1105
|View full text |Cite
|
Sign up to set email alerts
|

New Evidence on the State of Stress of the San Andreas Fault System

Abstract: Contemporary in situ tectonic stress indicators along the San Andreas fault system in central California show northeast-directed horizontal compression that is nearly perpendicular to the strike of the fault. Such compression explains recent uplift of the Coast Ranges and the numerous active reverse faults and folds that trend nearly parallel to the San Andreas and that are otherwise unexplainable in terms of strike-slip deformation. Fault-normal crustal compression in central California is proposed to result … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

39
445
3
1

Year Published

1990
1990
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 947 publications
(488 citation statements)
references
References 51 publications
39
445
3
1
Order By: Relevance
“…Under these conditions, the breakout orientation develops in the direction of the least principal horizontal stress. It has been previously demonstrated that stress orientations deduced from rock breakouts are consistent with other independent indicators (Bell and Gough, 1979;Zoback et al, 1988).…”
Section: Formation Microscanner Tool (Fms)supporting
confidence: 58%
“…Under these conditions, the breakout orientation develops in the direction of the least principal horizontal stress. It has been previously demonstrated that stress orientations deduced from rock breakouts are consistent with other independent indicators (Bell and Gough, 1979;Zoback et al, 1988).…”
Section: Formation Microscanner Tool (Fms)supporting
confidence: 58%
“…The fault has changed its location, at times stranding slivers of material [Sims, 1991]. The plate motion changed slightly about 3.5 Ma so that there is a compressional component [Harbert and Cox, 1989], generally taken up off the San Andreas fault [Zoback et al, 1987].…”
Section: Geologic Settingmentioning
confidence: 99%
“…In addition, the flow of fluids within larger fault zones, also controlled by the fault products contained within them, has major implications for fault zone mechanics. If high fluid pressures within faults zones can be maintained by low-permeability fault rocks for significant periods of time, then this will affect the overall strength of the fault zone, perhaps explaining observations such as the apparent low strength of the San Andreas fault system as suggested by the stress/heat flow paradox [Zoback et al, 1987;Lachenbruch and Sass, 1980]. Clay-bearing fault gouges are common constituents of large fault zones [Rutter et al, 1986;Miller, 1996] be present at depth to perhaps 10 km in currently active large faults [Wintsch et al, 1995;Hacker, 1997].…”
Section: Introductionmentioning
confidence: 99%